MAJOR DISEASES OF HAZELNUT (CORYLUS AVELLANA L.) IN THE CONDITIONS OF UZBEKISTAN AND MEASURES FOR THEIR CONTROL (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Hazelnut (Corylus avellana L.) cultivation in Uzbekistan is increasingly expanding due to its high nutritional value and economic significance. However, fungal and bacterial diseases are widely distributed and have a significant negative impact on plant growth, development, and yield. This study examines the major diseases affecting hazelnut under Uzbekistan’s climatic conditions, including powdery mildew (Phyllactinia guttata), leaf spot (Gloeosporium coryli), bacterial blight (Xanthomonas arboricola pv. corylina), and root rot (Armillaria spp.). Disease symptoms, causes of spread, and effects on productivity are analyzed. Recommendations for effective control measures, including preventive practices, agrotechnical interventions, and chemical treatments, are provided. The implementation of a scientifically based protection system ensures sustainable development and high yield of hazelnut plantations in the region.
Keywords: Hazelnut, disease, plant, control measures.